ANALYSIS FOR A SAILING SAFETY INFORMATION SYSTEM IN KARANGHARJO VILLAGE, KRAGAN SUBDISTRICT, REMBANG REGENCY - Danang Dwi Saputro; Widi Widayat; Feddy Setio Pribadi (IJMEA International Journal of Marine Engineering and Applications, 2026)
Karangharjo Village, located in Kragan Subdistrict, Rembang Regency, is a community where the majority of residents work as small-scale fishermen using vessels under 5 GT. These fishermen face a high risk of maritime accidents due to a limited understanding of and access to sailing safety technology. Based on a social mapping survey conducted in 2024, the village has 25 fishing groups with a total of 250 fishermen. Every year, maritime accidents occur, resulting in physical disabilities, fatalities, and an increasing number of orphans. Advanced satellite-based safety mitigation and navigation technologies, which are commonly used by larger vessels, are difficult for these small-scale fishermen to access due to informational and economic constraints. The Marine Affairs and Fisheries Agency of Rembang Regency states that 30% of maritime accidents are caused by a lack of information and inadequate navigation devices, a situation worsened by the fishermen's highly fluctuating income. The problems are formulated as follows: how can sailing safety technology be implemented for small-scale fishing groups, and how can an information system workflow be designed for maritime emergencies? The problem-solving approach for this research involves a needs analysis of small-scale fishermen and the development of an information block model for emergency response. Based on these issues, the objectives of this study are to reduce the rate of maritime accidents in Karangharjo Village and to accelerate the handling of emergency situations. This study uses a mixed-methods approach, combining quantitative and qualitative techniques with the Sustainable Livelihood Approach (SLA). The expected outputs of this research are a publication in an accredited international journal and a copyright, falling under the category of Key Performance Indicator (IKU) 5, as research results that are utilized by the community.